Results from Newberry Volcano EGS Demonstration, 2010–2014. (September 2016) - Cladouhos, Trenton T.; Petty, Susan; Swyer, Michael W.; Uddenberg, Matthew E.; Grasso, Kyla; Nordin, Yini
Highlights: 5 year project demonstrates recent technological advances for EGS development. Two years of permitting, technical planning, and development of a project-specific ISMP. Injectivity changes, thermal profiles and seismicity indicate enhanced fracture permeability. Microseismic event locations being analyzed to target production well. Thermally-degradable zonal isolation material blocked two zones and created two zone. Abstract: The Newberry Volcano EGS Demonstration is a 5 year field project designed to demonstrate recent technological advances for engineered geothermal systems (EGS) development. Advances in reservoir stimulation, diverter, and monitoring are being tested in a hot (>300 °C), dry well (NWG 55-29) drilled in 2008. These technologies could significantly reduce the cost of electrical power generation from geothermal resources. The project, funded in part by the Department of Energy, began in 2010 with two years of permitting, technical planning, and development of a project-specific Induced Seismicity Mitigation Plan (ISMP). Well stimulation carried out in 2012 indicated that casing repairs were needed; confirmed by further wellbore logging and analysis in 2013. Repairs were completed in August 2014, and the well was re-stimulated in the fall. 9500 m 3 (2.5 million gallons) of groundwater were injected at a maximum wellhead pressure of 195 bar (2850 psi) over 4 weeks of hydraulic stimulation. Injectivity changes, thermal profiles and seismicity indicate that fracture permeability in well NWG 55-29 was enhanced. The fifteen-station microseismic array (MSA) located 398 events in 2014, ranging in magnitude from M 0 to M 2.26. Temperature logs run after injection of thermally-degradable zonal isolation material (TZIM) showed that at least two flow zones were blocked and one or two new zones opened because of the injected TZIM. Break-down products of TZIM were detected in flow-back fluids, indicating that the material degraded as predicted. This work demonstrates the viability of large-volume low-pressure stimulation coupled with non-mechanical diverter technology and microseismic monitoring for reservoir mapping.